2017
DOI: 10.1111/resp.13177
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the breath sound spectrum during methacholine inhalation in children with asthma

Abstract: Background and objective: An effort-independent breath sound analysis is expected to be a safe and simple method for clinical assessment of changes in airway function. The effects of bronchoconstriction and bronchodilation on novel breath sound parameters in asthmatic children were investigated. Methods: The study population included 49 children with atopic asthma (male = 33; mean age: 10.2 years). We evaluated breath sound parameters of the highest frequency of the power spectrum (HFp), frequency limiting 50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In this study, there were no marked differences in any breath sound parameters, including F 99 , slope, A 3 /A T , B 4 /A T , RPF 50 and RPF 75 , between the infants with and without FW. A 3 /A T , RPF 50 and RPF 75 are decreased by methacholine inhalation and increased by β 2 agonist inhalation . It has been suggested that the induction of bronchial constriction changes the sound spectrum .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, there were no marked differences in any breath sound parameters, including F 99 , slope, A 3 /A T , B 4 /A T , RPF 50 and RPF 75 , between the infants with and without FW. A 3 /A T , RPF 50 and RPF 75 are decreased by methacholine inhalation and increased by β 2 agonist inhalation . It has been suggested that the induction of bronchial constriction changes the sound spectrum .…”
Section: Discussionmentioning
confidence: 99%
“…We recently investigated the potential utility of a breath sound analysis as a non‐invasive, reliable lung function test for children with asthma and infants . On analysis of a sound spectrogram, we identified and digitized the audible wheezing and FW in children .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tabata et al . used novel breath sound analysis in children with asthma undergoing methacholine challenge . Changes in specific breath sound parameters could be readily detected in the absence of overt wheezing.…”
Section: Asthmamentioning
confidence: 99%
“…Previous studies have demonstrated that airflow affects lung sound intensity in adults, 15 and due to the size difference between the airways of preterm and term infants, airflow may be different. Malmberg et al 16 and Tabata et al 17 were able to document changes in acoustic qualities of breath sounds during bronchoconstriction challenges in asthmatic children, with greater power at high frequencies during bronchoconstriction, suggesting an association between narrower airways and higher frequency power spectrum profiles. This could explain the higher power seen in the preterm group above 700 Hz, who inherently have narrower airways than the term cohort.…”
mentioning
confidence: 99%